2306. Molecular Epidemiology of and Risk Factors for Staphyloccus aureus (SA) Colonization in a Chinese Neonatal Intensive Care Unit (NICU). (26th November 2018) - Geng, Wenjing; McConville, Thomas; Hill-Ricciuti, Alexandra; Qi, Yujie; Saiman, Lisa; Uhlemann, Anne-Catrin
Abstract: Background: SA infections place a signiﬁcant burden on NICUs worldwide. However, little is known about the burden of SA in Chinese NICUs. In this study, we describe the molecular epidemiology of SA in the tertiary care 50-bed NICU of Beijing Children's Hospital and examine risk factors (RFs) for SA colonization in neonates. Methods: From May 2015 to March 2016, we prospectively collected nasal swabs from 536 neonates <28 days of age admitted from the community, perinatal services, or other hospitals. SA isolates were characterized by multilocus sequence type (MLST), staphylococcal chromosomal cassette mec ( SCCmec ) type, agr, spa-type, cytotoxicity and superantigen ( SAg ) genes. The characteristics of MRSA vs. MSSA and infecting vs. colonizing isolates were compared using Mann–Whitney U and Fisher's tests. Logistic regression was used to compare characteristics of infants colonized vs. uncolonized with SA. Results: We identified 96 (18%) and 23 (4%) neonates with SA colonization and/or infection on admission. Among the 96 colonized infants, 28 had MRSA and 68 had MSSA. ST59-SCCmecIVa-t437-agr-1 (20/28, 71%) and ST188-t189-agr-1 (11/68, 16%) were the common colonizing MRSA and MSSA clones, respectively. Among 23 isolates associated with infection, 17 were MRSA and ST59-SCCmecIVa-t437-agr-1 (6/17, 35%) was also the most common clone. Of the 119 SA isolates, 108 (91%) contained at least one SAg gene; however, none carried sasX . Cytotoxicity was significantly different among the main clones ( P = 0.04). While MRSA and MSSA had similar cytotoxicity (83.7% vs. 85.9%, P = 0.45), infecting isolates had higher cytotoxicity than colonizing isolates (87.6% vs. 84.5%, P < 0.01). Female sex (ORADJ = 2.05, P < 0.01), age >7 days (ORADJ = 7.14, P < 0.01), and vaginal delivery (ORADJ = 2.16, P < 0.01) were RFs for SA colonization, while antibiotic use was protective (ORADJ = 0.25, P < 0.01). Conclusion: SA colonization was common in infants admitted to our NICU and 2 clones predominated. MRSA and MSSA did not differ in cytotoxicity, although infecting isolates had higher cytotoxicity. Several non-modifiable risk factors for SA colonization were identified. Our results suggest that screening infants for SA is useful and interventions to target cytotoxic clones should be explored. Disclosures: A. C. Uhlemann, Merck: Investigator, Grant recipient.